Pixel‐Level Grayscale Manipulation to Improve Accuracy in Digital Light Processing 3D Printing. (12th February 2023) - Montgomery, S. Macrae; Demoly, Frédéric; Zhou, Kun; Qi, H. Jerry
Abstract: Digital light processing (DLP) is a widely used additive manufacturing technique for functional applications due to its high accuracy and print speeds. However, a variety of factors such as pixel size, motion stage resolution, optical focus, and chemical properties of the resin limit DLP's minimum resolution. Recently, research into locally varying light intensities has led to the emergence of grayscale DLP printing, which offers new capabilities including sub‐pixel manipulation of the printed shape. Here, a methodology is developed to enhance accuracy beyond what is typically capable for a given projector resolution by using pixel‐level grayscale control to create round features from sharp pixels. A numerical representation of the DLP pixel shape is developed to account for the effects of the incident light patterns. A reaction‐diffusion model is then used to predict the printed shapes before and after grayscale enhancement. This model is used to determine the optimal pixel intensities to match a target shape. Finally, the minimum feature size allowed by the proposed method is explored. The promising results represent an important step forward in raising DLP printing to higher accuracy, which will allow the fabrication of functional and structural components with smaller features or smoother faces. Abstract : Digital light processing is a widely used additive manufacturing technique due to its high accuracy and print speed. However, a variety of factors including pixel size limit the maximum accuracy of the technique. Here, a methodology is presented to enhance accuracy beyond what is typically capable for a given projector resolution by using pixel‐level grayscale control to create round features from sharp pixels.